2021
DOI: 10.15537/smj.2021.42.10.20210367
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implantation in post-lingual adults

Abstract: Objectives: To demonstrate the efficacy of cochlear implants (CI) in post-lingual adults, including surgical and auditory outcomes based on a 25-year experience at a tertiary referral hospital. Methods:This study was a retrospective, descriptive chart review of post-lingual adults, aged ≥18 years, implanted at King Abdullah Ear Specialist Center (KAESC), Kingdom of Saudi Arabia (KSA), between September 1994 and March 2020. The study included 176 cochlear implantations performed in 144 patients. Data retrieval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Of the included studies, 10 were retrospective [5][6][7][8][9][10][11][12][13][14], one was a cross-sectional study [15], three were case series [16][17][18], and three were case reports [19][20][21]. All studies were conducted in Saudi Arabia.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the included studies, 10 were retrospective [5][6][7][8][9][10][11][12][13][14], one was a cross-sectional study [15], three were case series [16][17][18], and three were case reports [19][20][21]. All studies were conducted in Saudi Arabia.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Surgical difficulties were reported in six patients (0.26%), either due to resistance to inserting an electrode due to causes such as intracochlear fibrosis, or due to other factors such as weakness of the posterior canal, injury to the auditory canal, and pain that required conversion to general anesthesia. Aljazeeri et al reported that dura accidental exposure and bleeding occurred in a total of three patients (0.13%) [ 5 ]. Aljazeeri et al also reported accidental facial nerve exposure in one case [ 5 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations